Effect of rainwater harvesting technologies on groundnutwheat cropping system in Hillocks area of watershed - KUMAR, HEMANT; KUMAR, MUNISH (Journal of Soil and Water Conservation, 2021)
An experiment was conducted during 2009-10 and 2010-11 at hillocks and valley watershed area of Amarpur-Bedaura-Chamraua, situated in block Babina, Jhansi, C.S.Azad University of Agriculture and Technology, Kanpur. The soil of experimental field was sandy loam locally known as Rakhar having low fertility status. The treatments comprised of conventional system, sowing across the slope, sowing on contour alignment, sowing in submergence bunding, sowing with dead furrows, sowing with vegetative hedge of local material and sowing in nala bunding area. These treatments were applied to groundnut and wheat under groundnut-wheat cropping system. The highest pod yield of groundnut of 28.70 q ha- 1 was reaped from sowing in nala bunding area in watershed. The sowing of wheat after groundnut in nala bunding area also gave highest grain yield of 42.66 q ha-1. The growth and yield traits of both the crops were concordant to the yields.